ANALISIS RESPON SISWA TERHADAP PENGEMBANGAN PERMAINAN OLAHRAGA TRADISIONAL YANG DIBAKUKAN DI MI NEGERI 1 PROBOLINGGO - Anggraini, Novitasari Yuli (Jurnal Kesehatan Olahraga, 2019)
AbstractThis research aims to determine the response of students against standardized of traditional sport games in MI Negeri 1 Probolinggo. Less response of students against traditional sport games given by the teachers who still focus on the other sport certain MI Negeri 1 Probolinggo is a reason of research.Descriptive research conducted using a data collection techniques in the form of questionnaires by survey method. This research using the subject between student of V and VI class MI Negeri 1 Probolinggo that 44 respondents. This research use of Pearson Product Moment to test validity of the 30 statements in the instruments have the result of 29 valid statements and 1 invalid statement.. Then one item of invalid statement is deleted.Function of Cronbach's Alpha formula to test reliability on instrument items and obtain a reliability coefficient value of 0.752 and all statements are reliable. The results of  this research indicate that the response of students against the development of the traditional sport games at MI Negeri 1 Probolinggo there is relationship signification between the response of students and standardized traditional sport games. It is proved by Person Correlation test with the r value = 0,877 > rtabel = 0,2973 and the signification value ( Sig. ) = 0,000 < 0,05. And strengthened by Spearment Correlation test with r value = 0,852> r table = 0,2973 and significance value (Sig.) = 0,000 <0,05. Then the hypothesis H0 rejected and H1 accepted.Based on the hypothesis that can be concluded that there is a correlation response of students against the traditional sport games on the students of V and VI class in MI Negeri 1 Probolinggo.Keywords: response of students, traditional sport games, Students of V and VI Class